DEVELOPMENT AND VALIDATION OF UV SPECTROPHOTOMETRIC METHOD AND RP-HPLC METHOD FOR ESTIMATION OF CAPECITABINE IN BULK AND TABLET DOSAGE FORMS - Pallavi, K.; Babu, P. Srinivasa; Babu, G. Kishore (International Journal of Applied Pharmaceutics, 2016)
Objective: The objective of the present work is to develop and validate a novel, specific, precise and reliable method for estimation of Capecitabine in bulk and pharmaceutical dosage form using UV-visible spectroscopy and RP-HPLC method. Methods: UV-visible spectrophotometric determination was performed with Elico double beam SL 210 UV-visible spectrophotometer having deuterium lamp at λmax 304 nm using water as a medium. Linearity was noted over a concentration range of 2-20 µg/ml with a correlation coefficient of 0.99. HPLC analysis was performed using Eclipse XDB C18 column with 5 µm particle size having dimensions 4.6 X 250 mm column, Agilent 1260 infinity DAD detector, 1260 infinity quaternary pump using Ezchrome software at a flow rate of 1 ml/min and a run time pressure of 2140 psi. Methanol: acetonitrile: water in the ratio 30: 30: 40 was used as mobile phase and the effluents were analyzed at 304 nm. Both the proposed methods were validated for various parameters like linearity, precision, accuracy, robustness, ruggedness, selectivity, detection, quantification limits, formulation analysis as per International Conference on Harmonization (ICH) guidelines. Results: Linearity for UV and HPLC method was noted over a concentration range of 2-100 µg/ml with a correlation coefficient of 0.99. The retention time was considered to be 4.60 min. The % RSD for interday and intraday precision studies and recovery analysis of both UV and HPLC methods was found to be less than 1% which is less than the official RSD limit (2%). Recovery analysis performed using marketed formulation capeguard was considered to be greater than 99% for both the methods. Conclusion: Both the methods developed were validated according to the ICH guidelines. Hence it was evident that the developed methods were novel, sensitive, precise and reliable for estimation of Capecitabine in bulk and were successfully applied for estimation of pharmaceutical dosage forms. Keywords: Capecitabine, UV-visible spectroscopic method, HPLC method, Validation